Association of FTO rs9939609, MC4R rs17782313, and TMEM18 rs6548238 Variants with Body Mass Index and Body Composition in Young Indonesian Adults - Erick Sidarta; Triyana Sari; Sari Mariyati Dewi Nataprawira; Ivan Christian Andianto; Meilani Kumala (The Indonesian Biomedical Journal, 2025)
BACKGROUND: Obesity is partly driven by genetic variation, including single-nucleotide polymorphisms (SNPs) in the Fat Mass and Obesity-associated (FTO), Melanocorti-4 Receptor (MC4R), and Transmembran Protein 18 (TMEM18) genes. However, only few Indonesian studies have integrated body composition analysis using bioelectrical impedance analysis (BIA) to evaluate the relationship between these genotypes and body mass index (BMI). Therefore, this study was conducted to investigate the association of FTO rs9939609, MC4R rs17782313, and TMEM18 rs6548238 with BMI and BIA-derived body composition parameters.METHODS: A cross-sectional study was conducted involving 111 healthy young adults aged 18–31 years olds. Subjects were examined for their body composition parameters using using the Quadscan 4000 BIA device, and then classified into obese (BMI≥25 kg/m2) and non-obese (BMI<25 kg/m2). Buccal rinse samples from each subjects were taken for the DNA extraction. Genotyping for FTO rs9939609, MC4R rs17782313, and TMEM18 rs6548238 were then performed using the Kompetitive Allele-Specific Polymerase Chain Reaction (KASPTM) method.RESULTS: Among 3 SNPs, only the A allele of FTO rs9939609 showed a significant association with increased BMI (p=0.0115) and several BIA parameters, including higher fat percentage (p=0.022), greater fat mass (p=0.0071), higher muscle mass (p=0.0334), and lower muscle mass percentage (p=0.022). Mediation analysis indicated that fat mass, fat-free mass index, body fat mass index, and total body water mediated 72.7–94.3% of the FTO effect on BMI, with an insignificant direct effect.CONCLUSION: FTO rs9939609 variant is significantly associated with higher BMI in Indonesia young adults, primarily mediated by alterations in fat and muscle mass. In contrast, MC4R rs17782313 and TMEM18 rs6548238 showed no significant associations. These findings underscore the value of integrating genetic profiling with BIA-based body composition measures to refine obesity risk assessment and clarify the regulatory role of the intronic FTO variant.KEYWORDS: FTO, MC4R, TMEM18, obesity, bioelectrical impedance analysis, genetic association, Indonesia